2022
DOI: 10.3389/fmed.2022.1060265
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in kidney transplantation-implications for immunosuppression and vaccination

Abstract: COVID-19 pandemic continues to challenge the transplant community, given increased morbidity and mortality associated with the disease and poor response to prevention measures such as vaccination. Transplant recipients have a diminished response to both mRNA and vector-based vaccines compared to dialysis and the general population. The currently available assays to measure response to vaccination includes commercially available antibody assays for anti-Spike Ab, or anti- Receptor Binding Domain Ab. Positive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Similarly, IgG production in vaccinated CVID and KTR patients was lower than hybrid immunized patients. Regarding cellular immune response, there is growing evidence showing that cellular immune response is much more preserved in solid organ transplant recipients than humoral immunity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, IgG production in vaccinated CVID and KTR patients was lower than hybrid immunized patients. Regarding cellular immune response, there is growing evidence showing that cellular immune response is much more preserved in solid organ transplant recipients than humoral immunity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, IgG production in vaccinated CVID and KTR patients was lower than hybrid immunized patients. Regarding cellular immune response, there is growing evidence showing that cellular immune response is much more preserved in solid organ transplant recipients than humoral immunity [24]. Some authors showed a severely impaired humoral response in immunodepressed and immunosuppressed patients even after several exposures of vaccine, but with a strong T-cell response.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine administration was found to reduce the mortality rate among SARS-CoV-2-infected KTRs ( 100 , 101 ). Mosconi et al ( 102 ) also confirmed the efficacy of COVID-19 vaccines in managing the risk of infection and enhancing clinical outcomes in individuals with compromised immune systems.…”
Section: Vaccination For Prevention Of Omicron Infection In Ktrsmentioning
confidence: 99%
“…Covid-19 results in a strong humoral and cellular immune response. 18 Antibodies (IgG and IgM) are classically detected in the second week of symptom onset, with IgM antibody appearing first and IgG being the most durable. Among the Covid-19 structural proteins, the Spike (S) and the Nucleocapsid (N) proteins are the main immunogens.…”
Section: Introductionmentioning
confidence: 99%